2003
DOI: 10.1007/s00442-002-1100-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brood parasitism on host reproductive success: evidence from larval interactions among dung beetles

Abstract: This paper investigates the effect of brood parasitism in a dung beetle assemblage in an arid region of Spain. The study was conducted during the spring season (March-May 1994-1998) using mesh cylinders buried into the ground, filled with sand and with sheep dung on top. We quantified the proportion of nests containing larvae of parasitic beetles and their effect on host larvae survival. Experiments on the effect of parasitic larvae on host-larvae survival were conducted by placing scarab brood masses (raised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…There is evidence that reproductive competition is a feature of female life histories in the genus Onthophagus; females have been found to exhibit intraspecific brood parasitism, raiding other females' brood balls, stealing dung or replacing existing eggs with their own, thereby exploiting a competitor's investment (Moczek & Cochrane 2006). Onthophagine females can also be victims of interspecific parasitism (González Megías & Sánchez-Piñ ero 2003). A female's probability of success in such encounters, whether it be defence of her own brood or attack of another female's, is likely to be strongly determined by her competitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that reproductive competition is a feature of female life histories in the genus Onthophagus; females have been found to exhibit intraspecific brood parasitism, raiding other females' brood balls, stealing dung or replacing existing eggs with their own, thereby exploiting a competitor's investment (Moczek & Cochrane 2006). Onthophagine females can also be victims of interspecific parasitism (González Megías & Sánchez-Piñ ero 2003). A female's probability of success in such encounters, whether it be defence of her own brood or attack of another female's, is likely to be strongly determined by her competitive ability.…”
Section: Discussionmentioning
confidence: 99%
“…Among the dominant Aphodiidae species, Euorodalus tersus and Mecynodes leucopterus are brood parasites in our study area, because rapid dung desiccation (46.5% water loss in 24 h) prevents endocoprid nesting (i.e., nesting within the dung). Thus, these species are able to actively locate and reach Scarabaeus and Onthophagus nests (González-Megías and Sánchez-Piñero, 2004). Field and laboratory experiments showed that brood parasitism by Aphodiidae affected 12% (Scarabaeus puncticollis nests) to 47% (Onthophagus merdarius) nests, causing high mortality (66%) of host larvae (González-Megías and Sánchez-Piñero, 2003).…”
Section: Detritivoreedetritivore Interactionsmentioning
confidence: 99%
“…Thus, these species are able to actively locate and reach Scarabaeus and Onthophagus nests (González-Megías and Sánchez-Piñero, 2004). Field and laboratory experiments showed that brood parasitism by Aphodiidae affected 12% (Scarabaeus puncticollis nests) to 47% (Onthophagus merdarius) nests, causing high mortality (66%) of host larvae (González-Megías and Sánchez-Piñero, 2003). Experimental manipulation of Onthophagus brood masses in the laboratory demonstrated that aphodiid larvae actively killed host larvae within the brood mass, although the dung-feeding aphodiid larvae did not consume the host larvae, but only killed them apparently to eliminate competing larvae of the host (González-Megías and Sánchez-PiñGonz ero, 2003).…”
Section: Detritivoreedetritivore Interactionsmentioning
confidence: 99%
“…Además del comportamiento típicamente endocóprido, algunas especies son capaces de construir primitivos nidos en el suelo (p.e. en el subgénero Colobopterus: Aphodius erraticus, Rojewski, 1983), otras presentan estados larvarios radicícolas, y otras incluso presentan comportamiento cleptoparasitos (es decir, aprovechan el momento de la construcción del nido para introducirse o depositar su huevo en las bolas creadas por otras especies; Cambefort & Hanski, 1991;Martín-Piera & Lobo, 1993;González-Megías & Sánchez-Piñero, 2003). Aunque Cambefort & Hanski (1991) consideran este último comportamiento poco significativo, estudios recientes demuestran que puede ser común cuando existen altas densidades de rodadores (Martín-Piera & Lobo, 1993), e incluso ser un factor importante en la estructuración de las comunidades coprófagas de ambientes mediterráneos semiáridos (González-Megías & Sánchez-Piñero, 2003), como los presentes en buena parte de la Península Ibérica.…”
Section: Sistemática Y Características Generales De Los Aphodiidae Ibunclassified